British Menopause Society consensus statement on the management of estrogen deficiency symptoms, arthralgia and menopause diagnosis in women treated for early breast cancer. Issue 1 (March 2019) - Marsden, Jo; Marsh, Mike; Rigg, Anne; ,
This guidance document by the British Menopause Society provides an overview of the management of women experiencing estrogen deficiency symptoms and arthralgia following a breast cancer diagnosis. It is now recommended that breast cancer patients are referred to health care professionals with an expertise in menopause for the management of such symptoms, which in turn often involves liaison with patients' breast cancer teams. However, as many women initially present to primary health care professionals for advice, this statement is aimed to support the latter in such consultations by providing information about symptom aetiology, current management strategies and controversies and identifying useful practice points.